An Analysis of Teachers’ Strategy in Teaching Listening - Nazla Ainun Kasim; Sri Rumiyatiningsih Luwiti (Magister Pendidikan Nonformal Pascasarjana Universitas Negeri Gorontalo, 2020)
Listening is the ways of picking up the information delivered by others in daily life, and also is the most important elements in studying foreign language. Several people have, however, problem in listening because they think that listening is the hardest skill to be mastered. To solve this barrier, teachers carry a big responsibility in their classroom. Teachers need to encourage students’ participation through preparing an interesting strategy during listening instruction in order to attract students’ attention to take part actively in listening. This study attempted to investigate the strategy used by teacher in teaching listening. Richard’s theory of listening strategy to include bottom-up and top-down was applied. Through utilizing qualitative descriptive analysis, this study involved three listening lecturers of English Department of Universitas Negeri Gorontalo where they were observed and interviewed. The analysis of data revealed that teachers used mostly top-down process activities in listening class.